Effects of Gamification in BCI Functional Rehabilitation - de Castro-Cros, Martí; Sebastian-Romagosa, Marc; Rodríguez-Serrano, Javier; Opisso, Eloy; Ochoa, Manel; Ortner, Rupert; Guger, Christoph; Tost, Dani (Frontiers in Neuroscience, 2020)
• Objective: To evaluate if introducing gamification in BCI rehabilitation of the upper limbs of post-stroke patients has a positive impact on their experience without altering their efficacy in creating motor mental images (MI). • Design: A game was designed on purpose and adapted to the pace and goals of an established BCI-rehabilitation protocol. Rehabilitation was based on a double feedback: functional electrostimulation and animation of a virtual avatar of the patient limbs. The game introduced a narrative on top this visual feedback with a virtual competitor (a rat character) and an external goal (protecting bits of cheese). A study was performed with 10 patients and a control group of 6 volunteers. Two rehabilitation sessions were done, each made of one stage of calibration and two training stages, some stages with the game and other without. The accuracy of the classification was taken as a measure to compare the efficacy of MI. Users’ opinions were gathered through a questionnaire. • Results: Gamified rehabilitation does not impact on the efficacy of MI, but it improves users experience making it more fun. • Conclusion: Game narratives can be in introduced in BCI rehabilitation to make it more gratifying and engaging.